Evaluation of Agroecological Performance Toward Sustainable Agriculture of Beni Municipality, Myagdi, Nepal - Pratima Regmi; Dhurba Banjade; Subodh Khanal; Bandana Paudel; Manisha Khatri; Asmi Poudel; Dipak Khanal; Aman Shrestha; Laxmi Prasad Joshi (AgroEnvironmental Sustainability)
This study assessed the effectiveness of agroecological farming practices in Beni municipality, Myagdi district, Nepal, by surveying 150 households. The analysis considered various sociodemographic factors, occupations, and ecological aspects to calculate the Characterization of Agroecological Transition (CAET) scores. Only 20 out of the 150 farms received CAET scores between 50-60%, categorizing them as “incipiently transitioning” toward agroecological practices. Three of the ten evaluated elements scored below 40%, while four scored below 50%, and the remaining three were under 60%, resulting in an overall average score of 43.39%. This low score indicates limited adoption of agroecological practices in the area. The highest CAET scores were associated with male farmers, individuals identifying as Brahmin, those with basic literacy, and farms involved in beekeeping, where beneficial pollinators were present. Beekeeping was significantly correlated with higher CAET scores and also linked with food self-sufficiency for daily needs. Additionally, significant differences in CAET scores were observed across gender, ethnicity, and involvement in beekeeping. The study concludes that while interest in agroecological practices exists, adoption is hampered by limited knowledge and socioeconomic challenges. To foster greater agroecological transitions, targeted education and support systems must be developed, with a focus on integrating beekeeping and promoting a pollinator-friendly environment.